Penerapan Program MBKM di Indonesia Ruang Lingkup Mahasiswa - Aziiza, Ishmadila Nahda; Nurmandi, Achmad; Fridayani, Helen Dian (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to evaluate the implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) program in Indonesia to improve the quality of higher education and provide opportunities for students to gain broader learning experiences. This program allows students to take courses outside their study program, do internships in industry, teach in schools, conduct research, and run humanitarian projects. The research method applied is a literature study approach, where data is collected from journal articles. In this study, the author used a qualitative descriptive method. Data analysis was carried out qualitatively with the help of Nvivo 12 software. The implementation of the MBKM program runs well if there is cooperation between students, lecturers, and educators in implementing the program. After the MBKM program began, many lecturers and students did not understand the essence of the MBKM policy. Therefore, information about the MBKM policy still needs to be optimized. Keywords: Students, Implementation, MBKM Program, Study Program